Dactylomonas gen. nov., a Novel Lineage of Heterolobosean Flagellates with Unique Ultrastructure, Closely Related to the Amoeba Selenaion koniopes Park, De Jonckheere & Simpson, 2012. (15th June 2018) - Hanousková, Pavla; Táborský, Petr; Čepička, Ivan
Abstract: We report the discovery of a new genus of heterolobosean flagellates, Dactylomonas gen. nov., with two species, D. venusta sp. nov. and D. crassa sp. nov. Phylogenetic analysis of the SSU rRNA gene showed that Dactylomonas is closely related to the amoeba Selenaion, the deepest‐branching lineage of Tetramitia. Dactylomonads possess two flagella, and ultrastructural studies revealed an unexpected organization of the flagellar apparatus, which resembled Pharyngomonada (the second lineage of Heterolobosea) instead of Tetramitia: basal bodies were orthogonal to each other and a putative root R1 was present in the mastigont. On the other hand, Dactylomonas displayed several features uncommon in Heterolobosea: a microtubular corset, a distinctive rostrum supported by the main part of the right microtubular root, a finger‐like projection on the proximal part of the recurrent flagellum, and absence of a ventral groove. In addition, Dactylomonas is anaerobic and seems to have lost mitochondrial cristae. Dactylomonas and Selenaion are accommodated in the family Selenaionidae fam. nov. and order Selenionida ord. nov. The taxonomy of Tetramitia is partially revised, and the family Neovahlkampfiidae fam. nov. is established.